The immune synapse: past, present, and future - Dustin, M; Baldari, C (Humana Press, 2017)
Immunological synapses are specialized cell-cell junctions characterized by (1) close apposition of the immune cell membrane with the membrane of another cell driven by adaptive or innate immune recognition, (2) adhesion, (3) stability, and (4) directed secretion. This phenomenon was first recognized in the 1970s and the early 1980s through electron microscopy of ex vivo functioning immune cells. Progressive advances in fluorescence microscopy and molecular immunology in the past 20 years have led to rapid progress on understanding the modes of cell-cell interaction and underlying molecular events. This volume contains a diverse range of protocols that can be applied to the study of the immunological synapses and related immune cell junctions both in vitro and in vivo; and in disease settings in animal models and humans. We have also included chapters on critical molecular tools such as protein expression and mRNA electroporation that underpin or expand imaging approaches, although they are not specific to the study of immune synapses. We hope that these chapters will be of use to people entering the field as well as seasoned practitioners looking to expand their repertoire of methods.